Formalist Criticism and Reader-Response Theory - - Mohammad Al Fuadi (RUDN Journal of Language Studies, Semiotics and Semantics, 2014)
The article deals with the interaction of formalism as a trend in language and literature studies, on the one hand, and a teaching method, a technique of teaching to understand and investigate literary text proceeding from its structure and content, on the other hand. One of the main principles is dialogism (M. Bakhtin) that creates the coeducation between the writer and reader. Thus the process becomes bilateral, or even multilateral and it includes criticism on both parts - a teacher and a student-reader as they are interpreting a literary text.